FINANCIAL DISTRESS PADA PERUSAHAAN REAL ESTATE DAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Ida Mustahgfiroh; G. Anggana Lisiantara (Jurnal Akuntansi dan Pajak, 2022)
Abstract This researcheri examinesi how profitability, liquidity, leverage, andi market ratios affect fiinanciali distress. Thei sample usedi is real estate and propertiyi companies listedi on the Indonesia Stocki Exchangei for the periodi 2016i to 2019. Thei samplingi methodi uses purposive samplingi so that 144i real estate andi property companies are obtained. This study uses paneli data regressioni analysisi tecihnique withi the help ofi Eviewsi 9. This studyi shows that the independenti variable profitabilityi has no significanti effect on financiali distress. Liquidityi has no effecti on financiali distress, Leveragei has a significanti positive effiecti on financiali distress, and Marketi Ratio has no effect oni financiali distress.